The Oxford Handbook of Deliberative Democracy 2018
DOI: 10.1093/oxfordhb/9780198747369.013.45
|View full text |Cite
|
Sign up to set email alerts
|

The Forms of Deliberative Communication

Abstract: As deliberative democratic theory has moved from a macro theory of democratic legitimacy to prescriptions for institutional design, questions about what constitutes deliberative communication have taken on increasing practical importance. At the same time, empirical data has accumulated to answer those questions. We review findings on the kinds of talk that produce either mutually-agreed upon decisions or better understanding of the issues at stake, equality among speakers, and impacts on policies or participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Earlier deliberative scholars, despite following distinct traditions, place the exchange of reasons at the core of deliberation. In subsequent debates on what type of communication is needed for deliberation (Young, 2000;Gabardi, 2001;Mouffe, 2005), a number of scholars have developed a more pluralistic approach to reasoned discussion, by acknowledging the merits of rhetoric, storytelling, performances, and humour that can lead to deliberation (Dryzek, 2000;Bächtiger et al, 2010;Dryzek and Hendriks, 2012;Mansbridge et al, 2012;Neblo, 2015;Polletta and Gardner, 2018). We place ourselves in line with those who argue that rational discussion is compatible with emotions and personal stories (Goodin, 2005;Ulbert and Risse, 2005;Thompson, 2008;Bächtiger et al, 2010;Steiner, 2012;Maia and Hauber, 2019).…”
Section: Reason-giving and Personal Stories In Deliberationmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier deliberative scholars, despite following distinct traditions, place the exchange of reasons at the core of deliberation. In subsequent debates on what type of communication is needed for deliberation (Young, 2000;Gabardi, 2001;Mouffe, 2005), a number of scholars have developed a more pluralistic approach to reasoned discussion, by acknowledging the merits of rhetoric, storytelling, performances, and humour that can lead to deliberation (Dryzek, 2000;Bächtiger et al, 2010;Dryzek and Hendriks, 2012;Mansbridge et al, 2012;Neblo, 2015;Polletta and Gardner, 2018). We place ourselves in line with those who argue that rational discussion is compatible with emotions and personal stories (Goodin, 2005;Ulbert and Risse, 2005;Thompson, 2008;Bächtiger et al, 2010;Steiner, 2012;Maia and Hauber, 2019).…”
Section: Reason-giving and Personal Stories In Deliberationmentioning
confidence: 99%
“…The studies of Elster (1998) and Steiner et al (2004) showed that political representatives tend to make more references to the common good when speaking in public than in discussions behind closed doors; and, therefore, report to the general public and advance proposals that might appear to be good for all, and not just for the speaker. Conversely, citizens frequently engage in discussions to discover adversarial positions in informal forums and they benefit from listening and learning from each other without expecting to exert influence on political decisions (Steiner, 2012;Bächtiger and Gerber, 2014;Gerber et al, 2016;Polletta and Gardner, 2018). Typically, ordinary people do not have the common good in mind when they express their arguments (Himmelroos, 2017).…”
Section: Contexts Of Deliberationmentioning
confidence: 99%
See 3 more Smart Citations